Integrated protocol for value-addition in strawberry (Fragaria x ananassa) (Current Horticulture, 2024)
An integrated protocol was standardized for production of diversified products from strawberry (Fragaria x ananassa). The fresh  fruits were subjected to lactic acid fermentation using Lactobacillus sp. The prepared probiotic drink was collected and left over  fruits were utilized for preparation of other products, viz. candy, squash, jelly and wine. Candy was prepared by incubating whole  fruits in subsequently increasing concentrations of sugar syrup and then drying at 60 oC temperature in electric dehydrator to an  intermediate moisture level of around 12%. The sugar syrup thus left had attractive red color due to anthocyanins extracted from the  fruits. It was used for preparation of squash, jelly and wine. The strawberry probiotic drink contained 2.2 oB TSS, 0.17% acidity, 2.1  mg/100ml vitamin-C, 37.1 mg/100ml phenolics and 2.36 mg/100ml anthocyanins. During ambient storage of probiotic drink up to  30 days, vitamin-C, phenolics and anthocyanin contents decreased while reducing sugars increased. Quality analysis of strawberry  products revealed that candy contained highest amounts of phenolics and anthocyanins followed by jam, jellly and squash and least  in wine. The vitamin-C content ranged between 1.6 to 14.8 mg/100 g or ml, being highest in jelly while least in wine. The ethanol  content in wine was found to be 11.7 per cent. All the strawberry products were highly acceptable during sensory evaluation scoring  above 7.0 out of total 9.0. It may be concluded that a variety of processed products could be prepared from same raw material by using  the integrated protocol for strawberry products.
Keywords: Strawberry; Probiotic; Fermentation; Lactobacillus; Anthocyanins